2014
DOI: 10.1148/rg.344140082
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal and Pelvic Complications of Nonoperative Oncologic Therapy

Abstract: Oncologic patients are treated with a combination of chemotherapy, radiation therapy, and surgery. Advances in therapeutic options have greatly improved the survival of patients with cancer. Examples of these advances are newer chemotherapeutic agents that target the cell receptors and advanced radiation therapy delivery systems. It is imperative that radiologists be aware of the variety of imaging findings seen after therapy in patients with cancer. Complications may occur with classic cytotoxic therapies (eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Cytotoxic agents exert antineoplastic activity by directly targeting DNA, RNA, intracellular proteins, or cell membranes of rapidly dividing cancer cells, resulting in cell death. The different classes of cytotoxic agents and their mechanisms of action are detailed in Table 1, while other systemic agents are discussed in Table 2 (2)(3)(4). The toxicity profiles of cytotoxic agents are usually dose dependent.…”
Section: Systemic Agents Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytotoxic agents exert antineoplastic activity by directly targeting DNA, RNA, intracellular proteins, or cell membranes of rapidly dividing cancer cells, resulting in cell death. The different classes of cytotoxic agents and their mechanisms of action are detailed in Table 1, while other systemic agents are discussed in Table 2 (2)(3)(4). The toxicity profiles of cytotoxic agents are usually dose dependent.…”
Section: Systemic Agents Backgroundmentioning
confidence: 99%
“…New immunologic agents stimulate the body's immune system to mount an antitumor response. Molecular targeted and immunologic agents are discussed in Table 3 (2,(6)(7)(8). The toxicity of these agents is not always cumulative or dose dependent.…”
Section: Systemic Agents Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…) and can enable to distinguish focal thickness from clots which appears hyperintense on T1WI. In the chronic phase, the bladder has a small volume and cannot be fully distended due to the fibrosis, appearing as a thin band of low signal intensity on T2WI on the inner aspect of the bladder wall . The distal ureters are less commonly affected by pelvic irradiation, but their involvement may cause stricture formation, resulting in hydroureter and, ultimately, hydronephrosis .…”
Section: Post‐crt Complicationsmentioning
confidence: 99%
“…It is well-known that chemotherapy and radiotherapy exert toxic effects on the intestinal mucosa [10]. Indeed, a non-controlled pilot-study demonstrated that a low FODMAP diet alleviated symptoms and improved the quality of life in cancer patients with radiation-induced acute intestinal injury [11], i.e., further evidence for a link between a high FODMAP intake and cancer-therapy-induced diarrhoea, thus encouraging us to examine if a low FODMAP diet could also benefit patients receiving chemotherapy.…”
Section: Introductionmentioning
confidence: 99%